Does Prior Percutaneous Coronary Intervention Adversely Affect Early and Mid-Term Survival After Coronary Artery Surgery? - Yap, C.; Yan, B.; Akowuah, E.; Dinh, D.; Smith, J.; Shardey, G.; Tatoulis, J.; Skillington, P.; Newcomb, A.; Mohajeri, M.; Pick, A.; Seevanayagam, S.; et al. (2009)
Objectives: To determine the association between previous percutaneous coronary intervention (PCI) and results after coronary artery bypass graft surgery (CABG). Background: Increasing numbers of patients undergoing CABG have previously undergone PCI. Methods: We analyzed consecutive first-time isolated CABG procedures within the Australasian Society of Cardiac and Thoracic Surgeons Database from June 2001 to May 2008. Logistic regression and propensity score analyses were used to assess the risk-adjusted impact of prior PCI on in-hospital mortality and major adverse cardiac events. Cox regression model was used to assess the effect of prior PCI on mid-term survival. Results: Of 13,184 patients who underwent CABG, 11,727 had no prior PCI and 1,457 had prior PCI. Mean follow-up was 3.3 ± 2.1 years. Patients without prior PCI had a higher EuroSCORE value (4.4 ± 3.3 vs. 3.6 ± 3.0, p < 0.001), were older, and more likely to have left main stem stenosis and recent myocardial infarction. There was no difference in unadjusted in-hospital mortality (1.65% vs. 1.55%, p = 0.78) or major adverse cardiac events (3.0% vs. 3.0%, p = 0.99) between patients with or without prior PCI. After adjustment, prior PCI was not a predictor of in-hospital (odds ratio: 1.22, 95% confidence interval [CI]: 0.76 to 2.0, p = 0.41) or mid-term mortality at 6-year follow-up (hazard ratio: 0.94, 95% CI: 0.75 to 1.18, p = 0.62). Conclusions: In this large registry study, prior PCI was not associated with increased short- or mid-term mortality after CABG. Good outcomes can be obtained in the group of patients undergoing CABG who have had previous PCI. © 2009 American College of Cardiology Foundation.